Association between internet use and primary headache severity among Hungarian university students: a cross-sectional study - Radvanyi, Ildiko; Tibold, Antal; Fejes, Eva; Mak, Kornel; Beke, Szilvia; Fehér, Gergely; Nyulas, Rita; Gaal, Valeria (Frontiers in Public Health, 2024)
BackgroundRecent studies suggest that increased digital technology usage could be a factor in the rising occurrence and severity of headache episodes. The purpose of this cross-sectional study was to determine whether the severity of primary headaches (migraine and tension-type headache) is associated with problematic internet use taking many covariates into account.MethodsWe conducted an online cross-sectional survey using a quantitative, descriptive questionnaire, targeting university students enrolled in correspondence courses, aged 18 to 65. The survey included socio-demographic parameters, risk factors, concomitant diseases, medical history of headaches, and details of online activities. Psychometric measurements contained the Problematic Internet Use Questionnaire, the 9-item short version of the Beck Depression Inventory (BDI-SF), and the Athens Insomnia Questionnaire.ResultsA total of 550 responders (n = 480 female; n = 70 male) completed the online questionnaire package. Among the participants, 202 individuals (36.7%) reported experiencing headaches, 74 had migraines and 119 had tension-type headache. Internet addiction was detected in 46 (8.4%) participants. Multivariate analysis of variance (MANOVA) showed that significant risk factors of all primary headaches severity included being <30 years (p = 0.044, OR = 3.439), not having children (p = 0.014, OR = 2.493), being married (p = 0.035, OR = 2.528), spending more than 4 h per day on the internet (p = 0.021, OR = 1.088), experiencing mood disturbances (p = 0.033, OR = 1.345) and the presence of insomnia (p = 0.048, OR = 1.667). Furthermore, a slight positive correlation was identified between the amount of time individuals spent on the Internet and the severity of headaches (r = 0.138, r2 = 0.019, ß = 1.068, p = 0.049). Patients with migraine or tension-type headache showed different predecessors, internet use was only associated with the severity of tension-type headache (night-time internet use, OR = 3.075, p = 0.043, and internet addiction, OR = 1.221, p = 0.003).ConclusionThis research marks one of the initial epidemiological investigations in Hungary concentrating on the possible adverse impact of online activities on the severity of headache. Although our study could find slight correlation between the role of online activities and internet addiction on the severity of primary headaches, the topic merits further investigation.